Characterization of human living myocardial slices culture-induced adaptations: a translational perspective - Jort S.A. van der Geest; Ernest Diez Benavente; Willem B. van Ham; Pieter A. Doevendans; Linda W. van Laake; Teun P. de Boer; Vasco Sampaio-Pinto; Joost P.G. Sluijter (Journal of Molecular and Cellular Cardiology Plus)
Heart failure involves complex pathophysiological processes, best studied in multicellular human cardiac tissues that reflect the native cellular composition and microenvironment. However, maintaining primary cells and tissues in culture for extended periods remains challenging. Developing robust human cardiac models is critical for advancing preclinical research and bridging the gap to clinical applications. This study aims to characterize adaptations occurring in human living myocardial slices (LMS) during ex vivo culture.During culture, LMS demonstrated progressive enhancements in contractile function including stronger force generation, reduced diastolic tension, and faster contraction-relaxation kinetics. However, excitability and force-frequency response decreased over the same period. Cultured LMS showed enhanced calcium handling, including increased ability to follow pacing, higher amplitude, and faster, more stable calcium re-uptake. Structurally, LMS displayed no changes in sarcomeres, cell-cell connections, or mitochondria, despite gene expression changes in cytoskeletal and extracellular matrix-related pathways. Transcriptomic analysis revealed metabolic activation with upregulation of metabolism-related pathways. Interestingly, LMS exhibited increased expression of genes associated with early cardiac development after the culture period.LMS provide a powerful translational model for cardiovascular research, enabling the evaluation of novel therapies and fundamental studies. However, culture-induced adaptations must be carefully considered when interpreting results to ensure physiological and disease relevance.